Exploring high multiplicity amplitudes: the QM analogue of the spontaneously broken case - Jaeckel, Joerg; Schenk, Sebastian (Arxiv, 2018)
Calculations of high multiplicity Higgs amplitudes exhibit a rapid growth that may signal an end of perturbative behavior or even the need for new physics phenomena. As a step towards this problem we consider the quantum mechanical equivalent of